Contribuição da eletrocoagulação no tratamento de efluentes visando o reuso de água na indústria do petróleo - Filipe Mattos Gonçalves (2019)
The present study investigated an evaluation efficiency of electrocoagulation (EC) for the pretreatment of a saline concentrated effluent from the reverse electrodialysis (C-EDR) stage from an oil refinery, aiming at water reuse in the industrial process. In this approach, an electrocoagulation system with 1 L capacity was set up for batch treatment using aluminum electrodes. Initially, experiments with a semi-synthetic C-EDR effluent were assessed for contaminants removal using fixed current density of 8.30 mA/cm2 and 1 cm distance between electrodes. The influence of initial pH (5 and 7), controlled temperature (20, 30 and 40 ºC) and operation time (60 and 120 min) on removal efficiency was investigated and solid residue were measured. The results showed that the optimum conditions were at pH 7 and 20-30◦C with removal rates around 70%, 57%, 10% and 44% for Ca, Sr, Na and COD, respectively. Thereafter, experiments were conducted with a real C-EDR using the best condition founded in preliminary tests, this time applying a current density of 5 and 10 mA/cm2 and 0.5 cm distance at room temperature (approximately 23◦C). Overall, the ideal condition for electrocoagulation treatment of C-EDR effluent was considered to be at room temperature (range 23 to 34°C), current density 5 mA/cm2, initial pH 7, 0.5 cm distance between electrode and during 120 minutes of operation, which showed removal of 81%, 65%, 23% and 21% of calcium, strontium, sodium and COD, respectively. This same condition presented electric operating cost about 2.4 times lower (3.96 R$/m3), in addition, the electrode consumption and sludge generation has halved, reaching 1,134g/L and 3,305g/L, representing a better cost- effective treatment in general.